(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
The text analyses the fundamental principle of the dignity of the human person and its performance as a general clause of protection of the personality. For that, it uses a descriptive and deductive methodology, based fundamentally on bibliographic and legislative research. The paper initially presents a brief evolution of the idea of dignity. It investigates the existential relation between the constitutionalisation of private law and the inclusion of the human dignity as a constitutional principle. It also examines the distinction between general clauses and principles, but makes it clear that the human dignity is, at the same time, a general clause and a principle. Finally, results demonstrate the importance of recognizing the human dignity as a true general clause of protection and promotion of the human person.